2018
DOI: 10.1093/infdis/jiy504
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Persistent Hepatitis E Virus Infection in Antibody-Deficient Patients Is Associated With Transfer of Antigen-Neutralizing Antibodies From Immunoglobulin Products

Abstract: The risk of persistent HEV infection in patients with antibody deficiency appears extremely low. This may be due to passive seroprotection afforded by the ubiquitous presence of anti-HEV in immunoglobulin replacement products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…A recent study determined HEV antibody titers in IG preparations and found all products reactive for HEV IgG 24 . This included a lot of KIOVIG, for which a titer of approximately 2.8 U/mL was determined, however, without information on geographic origin of the plasma used in manufacture, 24 whereas the titer of the KIOVIG lot fractionated exclusively from EU plasma that was used in the PBS experiment reported here was 7.6 U/mL.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A recent study determined HEV antibody titers in IG preparations and found all products reactive for HEV IgG 24 . This included a lot of KIOVIG, for which a titer of approximately 2.8 U/mL was determined, however, without information on geographic origin of the plasma used in manufacture, 24 whereas the titer of the KIOVIG lot fractionated exclusively from EU plasma that was used in the PBS experiment reported here was 7.6 U/mL.…”
Section: Discussionmentioning
confidence: 93%
“…The lower HEV prevalence in the United States was reflected in HEV antibody titers below the LOD in the eight US plasma‐derived intermediates tested, whereas only one in six EU plasma‐derived intermediates was below the LOD and HEV titers of 1.02 and 1.32 U/mL were determined for five EU plasma‐derived intermediates. A recent study determined HEV antibody titers in IG preparations and found all products reactive for HEV IgG 24 . This included a lot of KIOVIG, for which a titer of approximately 2.8 U/mL was determined, however, without information on geographic origin of the plasma used in manufacture, 24 whereas the titer of the KIOVIG lot fractionated exclusively from EU plasma that was used in the PBS experiment reported here was 7.6 U/mL.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hepatitis E virus appears to have a lower prevalence with fewer documented reports within inborn errors of immunity, which may be associated with the neutralising antibody in many infused immunoglobulin products [80]. There has been a recent case report of CVID patient with acute hepatitis owing to hepatitis E, which highlights the importance of maintaining vigilance even in those established on immunoglobulin replacement [81].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Other chronic viral hepatitides are described less commonly in these patient cohorts. We recently screened our antibody‐deficient patients for the presence of chronic hepatitis E but identified no patients, which may correlate with the presence of efficient neutralising antibody in many of the infused immunoglobulin products …”
Section: Hepacivirusesmentioning
confidence: 99%